Insights into tumor vaccines for elderly individuals in the context of immunosenescence - Li, Chenglong; Chen, Zhujun; Zhu, Changyu; Chen, Min; Li, Jinqi; Zhong, Lei; Hou, Yingying (Frontiers in Immunology, 2025)
The global burden of cancer is increasing tremendously, particularly among individuals aged 60 years and older, and has emerged as a critical public health concern. Cancer vaccine-induced immunity can recognize and eliminate tumor cells with high specificity and low toxicity. Nevertheless, immunosenescence increases the risk and severity of cancers in elderly individuals while impairing vaccine-induced immunity. Furthermore, much oncology research has predominantly focused on adults, often neglecting the potential contributions of aging individuals to tumor progression. Elucidating the interactions between the immunosenescent microenvironment and tumorigenesis can inspire the development of more effective cancer vaccines tailored to the characteristics of elderly individuals, thereby alleviating the global cancer burden. In this review, we analyze how the immunosenescent microenvironment impacts tumor development and summarize existing strategies aimed at enhancing cancer vaccine efficacy, drawing inspiration from insights into immunosenescence. We believe that this review will inspire efforts toward creating individualized cancer vaccines for the elderly.